Association between the nutrient profile system underpinning the Nutri-Score front-of-pack nutrition label and mortality in the SUN project: A prospective cohort study. Issue 3 (March 2021) - Gómez-Donoso, Clara; Martínez-González, Miguel Ángel; Perez-Cornago, Aurora; Sayón-Orea, Carmen; Martínez, J. Alfredo; Bes-Rastrollo, Maira
Summary: Background & aims: Front-of-pack nutrition labelling is a key public health policy that can be adopted as part of a comprehensive set of measures to promote healthy diets. The Nutri-Score, a five-colour summary label based on a modified version of the British Food Standards Agency Nutrient Profiling System (FSAm-NPS), is being considered for implementation in several European countries including Spain. This study aimed to prospectively assess the association between the FSAm-NPS and mortality rate in a Spanish cohort of university graduates. Methods: Analyses included 20 503 participants (mean [SD] age: 38 [12] years) from the SUN cohort. Dietary intake was assessed at baseline and after 10-years of follow-up with a validated semi-quantitative food-frequency questionnaire. The FSAm-NPS was calculated for each food/beverage based on their amount of energy, saturated fat, sugar, sodium, fibre, protein, fruits, vegetables, legumes, nuts, rapeseed, walnut and olive oils per 100 g of product. The FSAm-NPS Dietary Index (DI) was computed as an energy-weighted mean of the FSAm-NPS scores of all foods and beverages consumed by each participant. Multivariable-adjusted Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for all-cause and cause-specific mortality according to baseline and updated FSAm-NPS DI scores. Results: Over a median follow-up of 10.9 years, 407 participants died. A higher baseline FSAm-NPS DI score, reflecting consumption of foods with lower nutritional quality and hence less favourable Nutri-Score rating, was directly associated with all-cause mortality (HR Q4 versus Q1  = 1.82; 95% CI: 1.34 to 2.47; p-trend<0.001) and cancer mortality (HR: 2.44; 95% CI: 1.54 to 3.85; p-trend<0.001). No association was found for cardiovascular mortality. Conclusions: The consumption of food products with a higher FSAm-NPS score (lower nutritional quality) was associated with a higher rate of all-cause and cancer mortality in a large prospective cohort of Spanish, middle-aged university graduates. These findings further support the implementation of Nutri-Score in Euro-Mediterranean countries.